Dictionaries and Machine Translation: What Do Learners of Lithuanian as a Foreign Language Choose? - Valančiauskienė, Aušra (Vilnius University Open Series, 2023)
This article presents the results of research on using electronic dictionaries and machine translation tools when learning Lithuanian as a foreign language. The aim of this study was to indicate which dictionaries and machine translation tools are used for which purposes and what kinds of difficulties learners experience while using them. The research data were obtained by conducting an anonymous online poll in Lithuanian and English (using Google Forms). The questionnaire contained 15 questions. The participants in the study were chosen by way of availability sampling. The survey was carried out at Vilnius University in March 2023 with 67 respondents: 11 in Lithuanian and 56 in English. The study revealed that when learning Lithuanian as a foreign language, the respondents used both dictionaries and automatic translation tools. Most often, both tools were used for translation from and into Lithuanian. The types of language activities for which these tools were used were reading, writing, and partly listening. Only the respondents to English questionnaires used the mentioned tools for speaking. When learning Lithuanian, both monolingual and bilingual dictionaries were used, but monolingual dictionaries were used more than bilingual ones: 46.27% of respondents used monolingual dictionaries, and 31.34% used bilingual dictionaries. The study confirmed the researchers’ claim that monolingual dictionaries are used more by respondents with a higher level of language proficiency. Automatic translation tools were used by all respondents. The most popular of them is Google Translate, followed by DeepL. Other tools – Reverso, Bing Microsoft Translator, Systran Translate, Yandex Translate, and Lingea – are used by a few and only English questionnaire respondents. Dictionaries were consulted for the meaning of an unknown word, for synonyms, to confirm the meaning and spelling, to find usage examples, the field of the word used, and stress. Automatic translation is used for unknown words, phrases, and sentences to hear the pronunciation and find usage examples. The most common difficulties in using dictionaries were: unclear definitions of words and abbreviations; no text-to-speech function; too few usage examples; and unclear or missing examples. Weaknesses of automatic translation tools indicated by respondents: poor translation quality; lack of a search function; no examples of usage; no text-to-speech.